TREN GLOBAL DEEP LEARNING CURRICULUM DAN RELEVANSINYA BAGI PENGUATAN NILAI MODERASI DALAM PENDIDIKAN AGAMA ISLAM - Kurnia, Asraf; Kustati, Martin; Amelia, Rezki; Aisyah, Siti; Desfitri, Eni (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
The development of global education reflects a paradigm shift in curriculum design toward a deep learning approach, which emphasizes critical, reflective, and contextual learning. In the context of Islamic Religious Education (IRE), this approach creates opportunities to integrate religious moderation values in a transformative and relevant way in response to contemporary challenges. This study aims to examine global trends in deep learning curriculum and analyze its relevance to strengthening moderation values in IRE in Indonesia. This research employs a qualitative descriptive literature review of national and international publications between 2020 and 2024. The results reveal that deep learning strategies can foster students' critical thinking, tolerance, and adaptability in facing diversity. Scholars such as Michael Fullan and Andy Hargreaves are widely recognized for their work in deep learning education, while in the field of religious moderation in Indonesia, figures such as Siti Musdah Mulia, Nasaruddin Umar, and Budhy Munawar-Rachman have made significant contributions to promoting inclusive Islamic values. This study recommends integrating deep learning principles into the IRE curriculum as a strategy to develop a moderate, contextual, and socially responsive model of religious education.